2018
DOI: 10.1007/s11739-018-1817-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter embolotherapy of pulmonary artery aneurysms as emergency treatment of hemoptysis in Behcet patients: experience of a referral center and a review of the literature

Abstract: Hemoptysis is a life-threatening complication of Behcet's disease that is likely related to pulmonary artery aneurysm (PAA). Vascular interventional radiology may offer effective emergency therapeutic option, but has not been thoroughly investigated in this setting. A case series of a French referral center for hemoptysis combined with a literature review of case reports was conducted. Between 1995 and 2016, 12 patients were referred to our center for hemoptysis revealing or complicating the course of Behcet's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
10
0
3
Order By: Relevance
“…In patients refractory to this first-line treatment, anti-TNF-α agents (mainly infliximab) can represent a life-saving treatment (86). Eventually, embolisation, lobectomy, cavitectomy, and decortication can be considered (87)(88)(89).…”
Section: Arterial Involvementmentioning
confidence: 99%
“…In patients refractory to this first-line treatment, anti-TNF-α agents (mainly infliximab) can represent a life-saving treatment (86). Eventually, embolisation, lobectomy, cavitectomy, and decortication can be considered (87)(88)(89).…”
Section: Arterial Involvementmentioning
confidence: 99%
“…All patients with pulmonary artery involvement had hemoptysis. In a French study [13], hemoptysis was the inguinal symptom in 14 out of 17 patients with pulmonary artery aneurysm. As acute coronary syndrome and hemoptysis can both be severe and life-threatening, early diagnosis and appropriate treatment are required.…”
Section: Discussionmentioning
confidence: 98%
“…A case series of 17 patients with Behçet's disease found that embolization of pulmonary artery aneurysms was successful in achieving immediate control of hemoptysis in all patients. 5 Hemoptysis recurred in 41% of patients within 12 months, and one major complication was reported (acute exacerbation of preexisting pulmonary hypertension). 5 Coil erosion and migration into the mainstem bronchus is a rare complication of coil embolization with an unknown incidence, described in a case report occurring 2 years after embolization for which a left lower lobectomy with resection of the PAA and coil was performed.…”
Section: Discussionmentioning
confidence: 99%